A Systematic Review of the Diagnostic Accuracy of Depression Questionnaires for Cardiac Populations: IMPLICATIONS FOR CARDIAC REHABILITATION. Issue 6 (November 2019) - González-Roz, Alba; Gaalema, Diann E.; Pericot-Valverde, Irene; Elliott, Rebecca J.; Ades, Philip A.
Abstract : Purpose: Depression is overrepresented in patients with cardiovascular disease and increases risk for future cardiac events. Despite this, depression is not routinely assessed within cardiac rehabilitation. This systematic review sought to examine available depression questionnaires to use within the cardiac population. We assessed each instrument in terms of its capability to accurately identify depressed patients and its sensitivity to detect changes in depression after receiving cardiac rehabilitation. Methods: Citation searching of previous reviews, MEDLINE, PsycInfo, and PubMed was conducted. Results: The Beck Depression Inventory-II (BDI-II) and the Hospital Anxiety and Depression Scale (HADS-D) are among the most widely used questionnaires. Screening questionnaires appear to perform better at accurately identifying depression when using cut scores with high sensitivity and specificity for the cardiac population. The BDI-II and the HADS-D showed the best sensitivity and negative predictive values for detecting depression. The BDI-II, the HADS-D, the Center for Epidemiological Studies—Depression Scale, and the 15-item Geriatric Depression Scale best captured depression changes after cardiac rehabilitation delivery. Conclusions: The BDI-II is one of the most validated depression questionnaires within cardiac populations. Health practitioners should consider the BDI-II for depression screening and tracking purposes. In the event of time/cost constraints, a briefer 2-step procedure (the 2-item Patient Health Questionnaire, followed by the BDI-II, if positive) should be adopted. Given the emphasis on cut scores for depression diagnosis and limited available research across cardiac diagnoses, careful interpretation of these results should be done. Thoughtful use of questionnaires can help identify patients in need of referral or further treatment. Abstract : Depression questionnaires within cardiac populations are reviewed in depth. While the BDI-II and the HADS-D showed the most favorable properties for detecting depression, results suggest that the BDI-II should be used for monitoring purposes. A briefer approach comprising the PHQ-2, followed by the BDI-II might be best used for depression screening.